2009
DOI: 10.1139/t08-109
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and post-cyclic behavior of mixed clayey soils

Abstract: Soil structures are often comprised or supported by soils that are mixtures of cohesive and granular geomaterials. These soils are termed as intermediate or mixed soils and are widely found in natural deposits and man-made soil structures. The objective of this paper is to study the behavior of mixed clayey soils under monotonic, cyclic, and post-cyclic monotonic loading, with the main focus on the last of these three. For this purpose, a number of strain-controlled monotonic, cyclic, and post-cyclic triaxial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 11 publications
2
23
0
Order By: Relevance
“…This observation could be attributed to the higher shear strength of ST40, requiring a larger push to fully propagate the ruptures, and thus, generating higher pore pressures due to the increased compression. Monotonic undrained triaxial testing on these two materials [32] and other experimental findings [40] resulted in the same conclusion.…”
Section: T100 Versus St40 Materialssupporting
confidence: 64%
See 2 more Smart Citations
“…This observation could be attributed to the higher shear strength of ST40, requiring a larger push to fully propagate the ruptures, and thus, generating higher pore pressures due to the increased compression. Monotonic undrained triaxial testing on these two materials [32] and other experimental findings [40] resulted in the same conclusion.…”
Section: T100 Versus St40 Materialssupporting
confidence: 64%
“…The post peak behaviors of ST40 and T100 were studied thoroughly by Soroush and Soltani Jighe [32]; they showed that these cohesive materials do not exhibit strain softening behavior. However, dense granular soils, like the filter and shell materials, usually exhibit strain softening behavior.…”
Section: Soil Characteristics and Constitutive Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Soroush and Soltani-Jigheh [17] carried out strain-controlled cyclic triaxial testing on mixed clayey soils (clay-sand and claygravel mixtures), and the postcyclic soils not reconsolidated after cyclic loading. They concluded that the ratio of postcyclic undrained shear strength to initial undrained shear strength (S u(PC) /S u(M) ) and the ratio of postcyclic secant deformation modulus to initial secant deformation modulus (E 50(PC) /E 50(M) ) generally decreased as axial strain induced by cyclic loading increased.…”
Section: Research Backgroundmentioning
confidence: 99%
“…Vaid and Thomas (1995) found that the post-cyclic shear behavior become more closer to the initial performance of soil with less excess pore water pressure for limited liquefaction tests. Soroush and Soltani-Jigheh (2009) carried out lots of strain-controlled cyclic riaxial testing for mixed clayey soils (clay-sand and clay gravel mixtures). It was presented that S u(PC) /S u(M) (ratio of post-cyclic undrained shear strength to initial undrained shear strength) and E 50(PC) /E 50(M) (ratio of secant deformation modulus after post-cyclic test to initial secant deformation modulus) decreased generally as e c (cyclic strain) increased, and that the reduction in the deformation modulus was comparatively more pronounced.…”
Section: Introductionmentioning
confidence: 99%